Quantifying Heterogeneity of Testicular Histopathology in Men with Nonobstructive Azoospermia. Issue 5 (29th November 2021) - Punjani, Nahid; Flannigan, Ryan; Kang, Caroline; Khani, Francesca; Schlegel, Peter N.
Abstract : Purpose: We sought to determine if testicular histopathological heterogeneity is associated with sperm retrieval rates (SRRs) in men with nonobstructive azoospermia (NOA) who are undergoing microdissection testicular sperm extraction (mTESE). Materials and Methods: All patients undergoing mTESE by a single, high-volume surgeon at a tertiary infertility referral center between 2010 and 2020 were evaluated. Pathology reports from testis biopsy at the time of mTESE reported by fellowship-trained genitourinary pathologists were reviewed. Testicular heterogeneity was correlated to absolute SRRs. Logistic regression was used to determine if heterogeneity was associated with sperm retrieval. Results: A total of 918 men with mTESE were included. Of these, 391 men (43%) had 1 pathology, 388 men (42%) had 2, 108 (12%) had 3, and 31 (3.4%) had 4. Overall, the most common histopathology was Sertoli-cell only, followed by maturation arrest. The overall SRR was 42% with a clinical intrauterine gestation rate of 30%. Increasing histopathological variety was associated with higher SRRs (p <0.01); a SRR of 33% was observed when one histopathological subtype was present vs 94% with 4 subtypes. Furthermore, men with any foci of spermatogenesis had higher SRRs. Conclusions: In men with NOA, increasing testicular histopathological heterogeneity is correlated with higher SRRs driven by the identification of focal areas of spermatogenesis. This is an important, although predictable, observation. While diagnostic biopsy is not routinely required, these findings emphasize the value of having histology to perhaps predict the chance of sperm retrieval for future mTESE procedures.